Analisis Produksi Kepiting Bakau (Scylla seratta ) Kabupaten Bone - Masitah Masitah; Didi Rukmana; Budimawan Budimawan (AGRIMOR, 2019)
One of the biggest mangrove crab producing areas in Bone Regency is Cenrana District. The increase in the number of mangrove crab production in 2016 was the largest contribution of the Cenrana Subdistrict. However, as demand for mangrove crabs in Bone Regency continues to increase, the amount of production has not been able to meet the market demand for mangrove crabs even though their production has increased. This study aims to analyze the influence of production inputs (farmland, seeds, feed and labor) on the production of mangrove crabs. This research was conducted in Cenrana Subdistrict, Bone Regency, where the location was determined purposively. This research was conducted from February to March 2018. Respondents in this study were mangrove crab farmers who were selected using a sampling method of 92 people. The data analysis used is multiple regression analysis with the Ordinary Least Square (OLS) method, the model used is the Cobb-Douglas production function equation. The results showed that the increase in mangrove crab production was influenced by farmland factors (0,231), seeds (0,459), feed (0,155) and labor (0,238) and had a positive and significant effect on the production of mangrove crabs. Mangrove crab production will increase because there is a potential for increased production of mangrove crabs with the certainty of seed availability through improved mangrove habitat improvement, regulation of catching mangrove crab eggs laying eggs and environmental improvements due to pollution around the upper reaches of the Cenrana River Bone Regency.